The influence of the value clarification technique learning model on improving elementary school students' music creativity learning outcomes - Gayatri, Alifah Puspita; Sularso, Sularso; Enkhtungalag, Dash (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
In learning activities, creativity is an important aspect, where students can improve and develop their creative talents and abilities in thinking creatively. In grade III students of Muhammadiyah Al-Mujahidin Elementary School, Wonosari, there are still some students who are less interested in music art subjects. This study aims to determine the effect of theValue Clarification Technique (VCT) learning model on the musical creativity of grade III students, the efforts made by class teachers to improve musical creativity. This study is a descriptive quantitative study using an experimental method. The research design used is Pre-Experimental Design in the form of a One-Group Pretest-Posttest Design design with a sample of 24 students. Data collection techniques use test and non-test techniques, such as observation, interviews, and documentation. Data is processed using instrument validation and instrument reliability. The results of this study can be seen through the results of the hypothesis test with the Paired Sample t-test technique processed using the IBM SPSS for Windows version 30.0 program, the Sig value (2 Tailed) was obtained at 0.000, which means the Sig value 0.05, which means H0 is rejected and H1 is accepted. So it can be concluded that the Value Clarification Technique (VCT) learning model has an effect on the student’s outcome’s ability to play music creativity of grade III students in Muhammadiyah Al-Mujahidin Elementary School, Wonosari.